The Relationship Between ESG Scores and Cost of Debt – Evidence from the S&P 500 - Burger, Stefan (Department of Finance and Tax, 2023)
The purpose of this study was to determine the relationship between environmental, social, and governance (ESG) disclosure scores and a firm's cost of debt. Previous studies relating to ESG and cost of debt produced mixed results, with most finding that a relationship exists. Most of the research found superior ESG to decrease a company's credit risk and therefore borrowing rates. This was the relationship that this study expected. The study focused on all the companies on the Standard and Poor's 500 (S&P 500) that had both an ESG disclosure score and a cost of debt figure. The study collected panel data over a five-year period from 2016 to 2020. Fifty-six panel data regressions, including robustness checks were used to test the relationship between ESG and its components and cost of debt. The preferred regression model for ESG and its components from 2016 to 2020 was a panel data regression with fixed effects. In contrast to prior research, no material relationship was detected between ESG disclosures scores and the cost of debt of the sample companies for the period under consideration. Therefore, it was inferred that superior ESG does not decrease cost of debt for a company. It was found that liquidity and firm size variables – rather than ESG variables – had an influence on cost of debt. The findings of this study have both professional / real-world implications for investors and debt providers and academic implications for researchers. For professionals, including investors and debt providers, the results showed that ESG is not as advanced in the debt markets as previously perceived, owing to no relationship being found, and that ESG scores are more important to equity holders than to holders of debt. From the academic point of view, the results add to the existing body of knowledge and provide academics and researchers with an additional standpoint on the relationship between ESG and cost of debt.